Fungi as veritable tool in current advances in nanobiotechnology - Elijah A. Adebayo (Elsevier, 2021)
Fungi have great prospects for synthesis, applications and developing new products in nanotechnology. In recent times, fungi use in nanotechnology is gaining more attention because of the ecological friendly state of their metabolite-mediated nanoparticles, their safety, amenability and applications in diverse fields. The diversity of the metabolites such as enzymes, polysaccharide, polypeptide, protein and other macro-molecules has made fungi a veritable tool for nanoparticles synthesis. Mechanism of fungal nano-biosynthesis from the molecular perspective has been extensively studied through various investigations on its green synthesized metal nanoparticles. Fungal nanobiotechnology has been applied in agricultural, medical and industrial sectors for goods and services improvement and delivery to mankind. Agriculturally, it has found applications in plant disease management and production of environmentally friendly, non-toxic insecticides, fungicides to enhance agricultural production in general. Medically, diagnosis and treatment of diseases, especially of microbial origin have been improved with fungal nanoparticles through more efficient drug delivery systems with great benefits to pharmaceutical industries. This review therefore explored fungal nanobiotechnology; mechanism of synthesis, characterization and potential applications in various fields of human endeavours for goods and services delivery.